The trap of one perspective: a very subjective approach - Bilal, Nina (Przegląd Krytyczny, 2024)
In this paper I delve into the trap of one perspective relating to the concept of diversity via the reflection upon personal experiences and societal perceptions. Departing from traditional academic approaches I navigate through anecdotes and reflections, highlighting the dangers of a singular perspective. In the article structured into three sections—introduction, discussion, and conclusion—I examine the transformative potential of embracing diversity. From cultural exchanges to historical figures like Christopher Columbus, each narrative underscores the importance of diverse viewpoints. The aim is to provoke thought, inspire introspection, and spark meaningful dialogue, ultimately advocating for a more inclusive and empathetic society.